Effectiveness of fluconazole as antifungal prophylaxis in cancer patients undergoing chemotherapy, radiotherapy, or immunotherapy: systematic review and meta-analysis - Ramírez-Carmona, Wilmer [UNESP]; Fernandes, Gabriela Leal Peres [UNESP]; Díaz-Fabregat, Beatriz [UNESP]; Oliveira, Evelyn Carmo [UNESP]; do Prado, Rosana Leal; Pessan, Juliano Pelim [UNESP]; Monteiro, Douglas Roberto [UNESP] (Wiley, 2023)
This review assessed the effectiveness of fluconazole as antifungal prophylaxis on the incidence of oral fungal diseases in patients undergoing cancer treatment. The secondary outcomes evaluated were the adverse effects, discontinuation of cancer therapy due to oral fungal infection, mortality by a fungal infection, and the mean duration of antifungal prophylaxis. Twelve databases and records were searched. The RoB 2 and ROBINS I tools were used to assess the risk of bias. The relative risk (RR), risk difference, and standard mean difference (SMD) were applied with 95% confidence intervals (CI). The certainty of the evidence was determined by GRADE. Twenty-four studies were included in this systematic review. In randomized controlled trials pooling, fluconazole was a protective factor for the primary outcome (RR = 0.30; CI: 0.16, 0.55; p < 0.01, vs placebo). Compared to other antifungals, fluconazole was only more effective than the subgroup of amphotericin B and nystatin (alone or in combination) (RR = 0.19; CI: 0.09, 0.43; p < 0.01). Fluconazole was also a protective factor in non-randomized trials pooling (RR = 0.19; CI: 0.05, 0.78; p = 0.02, vs untreated). The results showed no significant differences for the secondary outcomes. The certainty of the evidence was low and very low. In conclusion, prophylactic antifungals are necessary during cancer treatment, and fluconazole was shown to be more effective in reducing oral fungal diseases only compared with the subgroup assessing amphotericin B and nystatin, administered alone or in combination.
Keywords: Amphotericin B; antifungal agents; chemoradiotherapy; head and neck neoplasms; leukemia; nystatin; oral candidiasis; stomatitis